Integrating digital transformation and servitization into digital servitization: A case on Domino's - Marasini Durga Prasad; Seong No Yoon; Donhee Lee (Global Business & Finance Review (GBFR), 2022)
Purpose: The purpose of this study is to suggest a digital servitization model which can be implemented by the restaurant industry and to explore the opportunities and challenges of digital servitization. Design/methodology/approach: The case study analysis method was applied for this research. Findings: This study reveals that pizza firms can gain competitive advantages and create value by implementing the digital servitization business model. In addition, firms can understand the opportunities and challenges of digital servitization and prepare themselves before implementing the business model. Research limitations/implications: Digital servitization model was proposed to analyze a single pizza company but a comparative study with other firms can be conducted to identify differences and create a common strategy. Originality/value: Firms commonly use an integrated digital transformation and servitization model to create customer value, but few case studies on integrated case models are available. This study investigates this research gap using a case study. The findings of this study have meaningful implications for restaurant managers to implement a digital servitization strategy.
Keywords: 650; Digital Transformation; Servitization; Digitalization; Digital Servitization; Competitive Advantages